2017
DOI: 10.1016/j.jmbbm.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy to enhance interfacial adhesion in fiber-reinforced calcium phosphate cement

Abstract: Calcium phosphate cements (CPCs) are extensively used as synthetic bone grafts, but their poor toughness limits their use to nonload-bearing applications. Reinforcement through introduction of fibers and yarns has been evaluated in various studies but always resulted in a decrease in elastic modulus or bending strength when compared to the CPC matrix. The aim of the present work was to improve the interfacial adhesion between fibers and matrix to obtain tougher biocompatible fiberreinforced calcium phosphate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Recently, it was revealed that the crystalline phase composition of sintered fish bone is similar to mineral phase of natural bone which is composed of HA at about 93 wt% and about 7 wt% of b-tricalcium phosphate (b-TCP). [11][12][13] The considerable research effort has been done to synthesize the novel CPs-polymer cement composites. The recently published review summarizes the literature on the production of HA from fish bones and discusses their potential applications in biomedical field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was revealed that the crystalline phase composition of sintered fish bone is similar to mineral phase of natural bone which is composed of HA at about 93 wt% and about 7 wt% of b-tricalcium phosphate (b-TCP). [11][12][13] The considerable research effort has been done to synthesize the novel CPs-polymer cement composites. The recently published review summarizes the literature on the production of HA from fish bones and discusses their potential applications in biomedical field.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of polymeric additives into cement liquid phase is the suitable way to fabricate a new CPC with the sufficient mechanical properties. [11][12][13] The considerable research effort has been done to synthesize the novel CPs-polymer cement composites. According to unique properties of natural polymer (eg, chitosan, alginate, starch etc.)…”
mentioning
confidence: 99%
“…However, the amide C=O bond and amide C-N bond shift to 1,537 cm -1 and 1,648 cm -1 , respectively, for tSF, implying a random form of SF chains. 30 These results indicate that the secondary structure of SF changes after treatment with the calcium hydroxide solution. Compared with SF, the tSF appears to have more random chains rather than β-sheets.…”
Section: Alk Treatment Of Sfmentioning
confidence: 78%
“…Different issues remain to be improved in CPC, such as mechanical properties – to more closely mimic those of natural bone. Modification with soluble polymers 30 and reinforcement with polymer and ceramic fibres 31 , 32 represent a step forward in this direction. Another aspect that has been the subject of extensive research is the adjustment of porosity as a strategy to enhance biological performance.…”
Section: Synthetic Bone Grafts: State Of the Artmentioning
confidence: 99%